Difference in Outcome Following Surgery for Native Aortic and Mitral Valve Infective Endocarditis - Kaartama, Tuukka; Nozohoor, Shahab; Johansson, Malin; Sjögren, Johan; Timane, Pedro; Ragnarsson, Sigurdur (The Thoracic and Cardiovascular Surgeon, 2019)
Background We investigated differences in clinical presentation, microbiology, and short- and long-term results according to the affected valve in patients who underwent surgery for left-sided native valve infective endocarditis (IE).Methods This was a single-center retrospective study of 117 patients with isolated mitral valve IE (group M) and 140 patients with isolated aortic valve IE (group A) who underwent surgery between 1998 and 2015.Results The mean age of patients in group M was 62 ± 14 years, whereas in group A the patients were 56 ± 14 years old (p = 0.001). There were 61 females (52% of patients) in group M and 31 females (22% of patients) in group A (p < 0.001). Abscesses were more common in group A than in group B. Staphylococcus aureus was more frequent in group M (47%, n = 55) than in group A (21%, n = 30; p < 0.001). The length of time from symptom onset to surgery was longer in group A than in group M, but the time from diagnosis to surgery was shorter in group A than in group M. Ninety-day mortality was similar in group M and group A in patients operated within 48 hours after diagnosis, but in patients who were operated more than 48 hours after diagnosis the 90-day mortality was 15% in group M and 3% in group A (p = 0.006).Conclusion There were considerable differences in preoperative characteristics, microbiology, timing of surgery, and outcomes between patients who underwent surgery for isolated aortic valve IE and those who were operated for isolated mitral valve IE.
Keywords: endocarditis; heart valve surgery; outcomes; mortality; morbidity